Assessment of soil quality indexes for different land use types in typical steppe in the loess hilly area, China. (November 2020) - Zhou, Yao; Ma, Hongbin; Xie, Yingzhong; Jia, Xiyang; Su, Tingting; Li, Jianping; Shen, Yan
Highlights: SQIs were calculated by three indicator selection methods and two scoring methods. The six SQIs were significantly positively correlated with each other. SQI-LRM was regarded as the most appropriate method to calculate the SQI. Abstract: Soil quality indexes (SQIs) are important for evaluating grassland ecosystems. The objective of this study was to assess different land-use soil quality using total data set, minimum data set (MDS), and revised minimum data set (RMDS) indicator selection methods and linear and non-linear scoring methods. Four land-use, which were including grazing grassland (GG), fencing grassland (FG), contour trench grassland (CG) and fish-scale pits grassland (FPG) in a typical steppe of loess hilly area in Ningxia, were taken as the research object. Eighteen indicators (soil bulk density; GMD: geometric mean diameter; MWD: mean weight diameter; FWC: field water-storage capacity; capillary porosity; total porosity; soil organic carbon; TN: total nitrogen; total phosphorus; AK: available potassium; available nitrogen; microbial biomass carbon; microbial biomass nitrogen; SA: sucrase activity; protease activity; CA: catalase activity; PPA: phosphatase activity; and urease activity) of soil physical, chemical, and biological characteristics of the 0–40 cm soil layer under different land use types were measured. Principal component analysis was used to select the MDS and RMDS. The results showed that three (SA, MWD, and PPA) and six (FWC, GMD, TN, AK, SA, and CA) soil indicators were included in the MDS and RMDS, respectively. The agreement values of SQIs for the linear scoring method were higher than those of the non-linear scoring method. The linear scoring-revised minimum data set was regarded as the most appropriate method to calculate the SQI because of its highest F and CV (Coefficient of Variation) values and correlation coefficient. The ranking of the SQI values of the four land use types was FG > GG > CG > FPG. The results showed that FG is the most beneficial measure for the restoration of degraded grassland, which has important guiding significance for the ecological construction of degraded grassland in the study area.